APOS Theory and Relational Understanding: A Systematic Literature Review - Riyadi; Diari Indriati; Farida Nurhasanah; Anastasya Ramadiana (FKIP Universitas Mataram, 2026)
Relational understanding is an essential skill that reflects students' mastery of the relationships between mathematical concepts, while APOS Theory provides a framework for analyzing the mental construction of this understanding. This study aims to identify and compare the application of APOS Theory and relational understanding in the context of mathematics learning. This study used the Systematic Literature Review (SLR) method based on the PRISMA framework. The literature search was conducted in the Scopus and Google Scholar databases with publications limited to 2014 to 2024, focused on elementary and secondary school levels. Of the 228 identified studies, 11 empirical articles were selected for analysis. The review results showed significant differences in the focus of the material; APOS Theory is predominantly applied to number topics and is often used as a basis for developing assessment instruments. In contrast, relational understanding is more widely studied in algebra topics. Furthermore, it was found that the problem-solving approach is a major factor influencing the formation of students' relational understanding. These findings offer educators insights into selecting pedagogical approaches that are suitable for the material's characteristics.